SPEAKING SKILL IMPROVEMENT THROUGH LANGUAGE GAMES, A Paper Presented In Regular Seminar of Lectures of English - Nurjanah Nurjanah (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2010)
The paper aims to present an idea for one problem of language teaching, namely the one aims to develop students’ ability in speaking English. It is the teaching through language games. Focus of the paper is to discuss about students’ ability in speaking English, especially for students of elementary schools. The writer is interested in writing this topic because she fells that speaking skill is the most important language skill when the students study General English, such as the one which is taught in general schools: Elementary, Junior, and Senior High schools. The writer, in this paper encloses the result of her research in her own school, conducted to students of Elementary School students. Here is the result, “Learning to speak English through games is able to improve students' skills in speaking. Students begin to feel confident to pronounce English words correctly”. Keywords : teaching, games, speaking skill.